The Implementation of Natural Environment-Based Islamic Education Learning at Citra Alam Elementary School, Cianjur Jakarta. - Defi Firmansyah; Indah Wulandari (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
In the process of education and learning as it takes place in an educational institution, components can be found that help in realizing the teaching and learning process, including the existence of media, methods and a good school atmosphere, which can bring success to the teaching and learning process so that the expected goals are achieved. Citra Alam Elementary School, Ciganjur Jakarta, is an Islamic educational institution that has a good, beautiful and healthy natural atmosphere. So that the nature around the school is a major supporting factor in the implementation of learning. One of them is in implementing Islamic religious education learning that uses nature as a learning medium so that students have the potential to carry out exploratory and fun learning and create a comfortable learning environment.This type of research is a field study research with a descriptive discussion of qualitative analysis, the data collection techniques used are: (1) Interviews, which are conducted with school principals, curriculum representatives and teachers of Islamic religious education related to the implementation of nature-based Islamic religious education learning. at Citra Alam Elementary School Ciganjur, Jakarta. (2) observation technique. (3) Documentary technique, to obtain data about the general picture of the school. Meanwhile, the data analysis method is the Miles and Huberman model data analysis which covers three steps in the research, namely data reduction, data presentation and conclusion.From the results of the study it can be concluded that: (1) The implementation of Islamic religious education learning taught in natural image elementary schools is carried out once a week with a duration of two hours, integrating the elements of Islamic Islamic education lesson values with other subjects, integrating religious education material Islam with routine activities at school such as camping, loving the environment, educational Ramadan activities, and utilizing natural resources such as caring for plants and making fertilizers. (2) Supporting factors in the implementation of nature-based Islamic religious education at Citra Alam Elementary School Ciganjur, Jakarta. Among them: utilizing nature as a learning medium, cooperative parents, competent teachers in their fields, and programs designed to connect students with nature. While the inhibiting factors include: the presence of teachers who are less open with their minds, lack of cooperation with others in preparing lessons, lack of an adventurous spirit, the presence of teachers who often come in and out so that program explanations need to be done repeatedly.Based on the results of this study, it is hoped that (1) Citra Alam Elementary School will always maintain good things and positive values related to the implementation of learning and the supporting factors that exist in nature-based Islamic religious education material, and also evaluate the inhibiting factors that occur. (2) Teachers of Islamic religious education materials to always improve their competencies so that they can always create Islamic religious education learning with the right media and a comfortable and pleasant learning atmosphere. (3) Researchers who will come to discuss this issue in more detail and better than ever.